Arqueologia da paisagem caieirista no município de Parnamirim/PE - Ferreira, Catarina Menezes (2018)
This study seeks to understand the landscape through the artisanal activity of lime in the Municipality of Parnamirim, located in the central wilderness of Pernambuco. The examination is focused on aspects of the daily life of the region that can be discussed from particularities of recent history. The intention is to analyze the landscape through the materiality and oral testimonies of the lime producers. The relations of people with things are focused to discuss notions of the limely activities and use of lime through social practices, in a context in which the importance of the incorporation of the studied landscape is emphasized. Through the subjectivity of the people involved in the documentation I look for the interpretation of the landscape that active subjects perceive, act and give meaning through a handmade production. In this way, I direct the research by gathering information about the lore, the materiality and memories present in the oral sources, the experience obtained by me in the field and my interpretation of scholars who discuss the landscape as a social environment. The perspective of active participation of the people is a central aspect of the discussion and involves directing the activities carried out in the region to the aspects of the individuals' permanence, which present ways of conceiving the landscape influenced by economic activities. This is a question captured by the way of understanding the landscape as an element inherent in the daily life of the local inhabitants. One of the arguments is that it is possible to know the social subjects surveyed on the basis of how they act in the landscape. It is an aspect of local socialization perceptible by the ways that those workers affirm their choice to remain in their place.